Accelerated Membrane Durability Testing of Heavy Duty Fuel Cells. Issue 1 (1st January 2015) - Macauley, Natalia; Alavijeh, Alireza Sadeghi; Watson, Mark; Kolodziej, Joanna; Lauritzen, Michael; Knights, Shanna; Wang, Gary; Kjeang, Erik
Abstract : Regular durability testing of heavy duty fuel cell systems for transit bus application requires several thousand hours of operation, which is costly and time consuming. Alternatively, accelerated durability tests are able to generate failure modes observed in field operation in a compressed time period, by applying enhanced levels of stress. The objective of the present work is to design and validate an accelerated membrane durability test (AMDT) for heavy duty fuel cells under bus related conditions. The proposed AMDT generates bus relevant membrane failure modes in a few hundred hours, which is more than an order of magnitude faster than for regular duty cycle testing. Elevated voltage, temperature, and oxidant levels are used to accelerate membrane chemical stress, while relative humidity (RH) cycling is used to induce mechanical stress. RH cycling is found to significantly reduce membrane life-time compared to constant RH conditions. The role of a platinum band in the membrane is investigated and membranes with Pt bands demonstrate a considerable life-time extension under AMDT conditions, with minimal membrane degradation. Overall, this research serves to establish a benchmark AMDT that can rapidly and reliably evaluate membrane stability under simulated heavy duty fuel cell conditions.